EGS P09 An Ambulatory General Surgical Service, Reducing the On-Call Burden and Improving Patient Experience. (7th December 2022) - Boag, Katie; Bradley, Alex; Toogood, Giles; Peckham-Cooper, Adam
Abstract: Background: The management of acute General Surgical patients is dramatically changing with the emergence of Emergency General Surgery departments. The trend is moving towards consultant-led services, and managing patients on ambulatory pathways. This prospective study aims to demonstrate the impact of a consultant-led ambulatory surgical clinic and primary care telephone access on the acute surgical take in a busy tertiary hospital. Methods: Data was collected from March 2021-March 2022. Patients were included via the primary care access line, as well as patient attendances either via surgical assessment unit (SAU), or ambulatory surgical clinic (ASC). Their pathways were recorded i.e. admit, discharge, further ambulatory investigation, listed for surgery. Results: Consultants took 6, 948 calls from primary care from March 2021–22. 43.7% of patients were given an appointment for ASC, 37.3% admitted to SAU, 3.5% directed to ED, and 15.5% given advice or redirected elsewhere. 54.6% of those seen in ASC were discharged without further follow up, the other 45.4% were either admitted, followed up or added to a waiting list. General Surgery patient attendances to SAU fell from an average of 1020 per month between March to October 2021 to 542 attendances November 2021 to present. Conclusions: The introduction of a consultant-led ambulatory service has reduced the on-call burden by half. The dramatic reduction in SAU attendances is likely to be the result of developed ambulatory pathways, improved communication with primary care and Consultant Emergency General Surgeons, and autonomy of Junior Surgical Trainees to redirect ED referrals onto refined and supported ambulatory pathways. A Consultant-led primary care access line has reduced ED attendances and allowed for effective streaming of patients. These changes have improved the patient experience significantly, by directing them straight to specialty with same or next day consultant clinics, and reduced waiting times overall. There has been a significant reduction in complaints and consistent improvement in patient feedback.